PENGARUH POLITICAL BACKGROUND DAN PENGETAHUAN DEWAN TENTANG ANGGARAN TERHADAP PENGAWASAN KEUANGAN DAERAH (Studi Empiris Pada DPRD Kabupaten Kepulauan Aru Dan Kota Tual) - Silooy, Revy Wilhelmina (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2022)
The main objective of this study is to empirically examine the influence of political background and council knowledge about the budget on regional financial supervision at the DPRD of Aru Islands Regency and Tual City. At the same time, the samples were 44 members of the DPRD of the Aru Islands Regency and Tual City. Census is the sampling technique used in this study. The analytical tool used is multiple linear regression. The results of the survey prove that political background has a significant effect on regional financial supervision. The board's knowledge of the budget substantially impacts provincial financial management